2021
DOI: 10.31557/apjcp.2021.22.4.1239
|View full text |Cite
|
Sign up to set email alerts
|

Association of Righ-Risk Human Papillomavirus and Ureaplasma parvum Co-Infections with Increased Risk of Low-Grade Squamous Intraepithelial Cervical Lesions

Abstract: Objective: The present report investigated the rates of coinfections between high-rik human papillomavirus (hrHPV) and the most important human mycoplasmas including Mycoplasma hominis, M. genitalium, Ureaplasma urealyticum and U. parvum in cervical samples of asymptomatic brazilian population. Methods: Were included a total of 283 women aged 25-64 years screened by Papanicolaou smears for determining cervical abnormalities, single-target polymerase chain reaction (PCR) and real-time PCR (rt-PCR) for hrHPV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…UP was the most prevalent pathogen in our study with over 50% positive cases amongst all women, and without significant variation regarding age. The data analysis revealed that despite its high prevalence UP was not significantly associated with Hr‐HPV infection while it seems to provide a tendency for protection of the development of ASC‐H/HSIL ( p = 0.074; OR = 0.74), which seems to be consistent with reports from other authors 56–61 . Similarly, to UP, UU was distributed equally independent of age.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…UP was the most prevalent pathogen in our study with over 50% positive cases amongst all women, and without significant variation regarding age. The data analysis revealed that despite its high prevalence UP was not significantly associated with Hr‐HPV infection while it seems to provide a tendency for protection of the development of ASC‐H/HSIL ( p = 0.074; OR = 0.74), which seems to be consistent with reports from other authors 56–61 . Similarly, to UP, UU was distributed equally independent of age.…”
Section: Discussionsupporting
confidence: 88%
“…The data analysis revealed that despite its high prevalence UP was not significantly associated with Hr-HPV infection while it seems to provide a tendency for protection of the development of ASC-H/ HSIL (p = 0.074; OR = 0.74), which seems to be consistent with reports from other authors. [56][57][58][59][60][61] Similarly, to UP, UU was distributed equally independent of age. Nevertheless, UU, which is mostly asymptomatic but described as associated with obstetric complications and HPV infection, 60,[62][63][64] revealed to be frequently associated with Hr-HPV multiple infections (p = 0.001; RR = 1.94).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Drago et al (Drago et al, 2016 proposed that UP is a possible HPV-induced CIN enhancer agent, and confirmed this in a study 5 years later, showing that UP infection is a risk factor for persistent genital HPV infection (Ciccarese et al, 2021). In their study of 283 patients, Noma et al (Noma et al, 2021) found that UP and HR-HPV coinfection increased LSIL risk. Similarly, a study of 480 patients found that UP14 and HR-HPV coinfection increased HSIL and cervical cancer risks, as did UP1 coinfection (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
“…In their study of 283 patients, Noma et al. ( Noma et al., 2021 ) found that UP and HR-HPV coinfection increased LSIL risk. Similarly, a study of 480 patients found that UP14 and HR-HPV coinfection increased HSIL and cervical cancer risks, as did UP1 coinfection ( Wang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal microbiota plays a role in the acquisition and persistence of HPV in the human vagina and the subsequent development and progression of cervical intraepithelial neoplasia. Noma et al (2021) found no significant association between M. genitalium and high-risk HPV infection. However, this was a statistical investigation of a small sample.…”
Section: Mycoplasma Genitalium and The Female Reproductive S...mentioning
confidence: 65%